Generation, Diagnosis and Application of Femtosecond Electron Single Bunch - SAKAI, Fumio; UESAKA, Mitsuru; KOTAKI, Hideyuki; YOSHII, Koji; DEWA, Hideki; KINOSHITA, Kenichi; HARANO, Hideki; UEDA, Toru; KANDO, Masaki; NAKAJIMA, Kazuhisa; KONDO, Shuji; WATANABE, Takahiro; et al. (Journal of the Atomic Energy Society of Japan / Atomic Energy Society of Japan, 2000)
A new S-band laser photocathode RF gun and chicane-type magnetic pulse compressor were installed in the twin linac system of Nuclear Engineering Research Laboratory, University of Tokyo. Low emittance (6πmm. mrad) femtosecond (240-290fs at FWHM) electron single bunch of 16MeV, 2% energy spread and 350pC/bunch was obtained. Femtosecond streak camera (200fs resolution) with dispersionless reflective optics, coherent transition radiation interferometer and far-infrared polychromator were used. We conclude that the streak camera and polychromator are the best for longer than 200fs (FWHM) bunch and for shorter, respectively. Detailed performances of the RF gun including the linac-laser synchronization and the reduction of dark currents were precisely evaluated. Further, we tried a new femtosecond quantum beam based pump-and-probe analysis, which is the time-resolved X-ray diffraction to visualize atomic motions. X-ray diffraction patterns of CuKα 1.2 from several monocrystal such as GaAs, KCl, CaF 2 were obtained using 10ps X-ray pulses. The visualization is under way. Finally, we introduce the new femtosecond ultrafast quantum phenomena research facility.